Factibilidad técnico económico de un centro de revisión vehícular en el cantón Quevedo - Vivanco España, Stalín Eduardo (2019)
The purpose of this research project is to carry out an economic technical feasibility study of a Vehicle Technical Review Centre (CRTV) in the canton of Quevedo of the province of Los Ríos-Ecuador, for future implementation; in order to: control the mechanical condition, safety systems, excessive noise, emission of gases, which causes the vehicles generating excessive pollution to the environment causing respiratory diseases, as a second point reduce accidents of traffic caused by damage to the systems that make up an automobile since the current Vehicle Review is carried out visually, empirically without being governed by technical standards for the correct vehicle functionality. Through field research that will include technical visits to the CRTV of the canton Santo Domingo in order to know each of the equipment, processes and times that are carried out at the time of the Vehicle Technical Review (RTV) to each type of vehicle. With the use of FlexSim software friendly tool to simulate processes in an ideal way, to optimize the working times and occupation of the operators and equipment that make up each of the processes that are carried out in the RTV. With the total number of the car park in the canton Of Quevedo, calculate the sample size in order to know the number of mechanical workshops to be surveyed (68 workshops) and to collect information on what are the most frequent mechanical failures of the Automotive. The study of economic feasibility has calculated the costs, revenue generated by CRTV with a projection of 5 years of operation. The estimated investment for construction in the first phase and adequacy will be $350,000 with a gross in the first year of operation of $583,769.92. Keywords: Feasibility, Technical, Economic, Vehicle Review Center